STRATEGI PENINGKATAN ESKPOR INDONESIA: MENGHADAPI TANTANGAN GLOBAL DENGAN TEORI PERDAGANGAN - Sari Wildani Guci; Ranah Santri Dongoran, Sakinatul Rahmi, Ahmad Rasyid; Dwita Sakuntala (CV. ADIBA AISHA AMIRA, 2025)
Analysis of Indonesia's export performance from 2018 to 2023 shows significant fluctuations with the highest peak in 2022 reaching USD 292.6 billion, driven by strong global demand and high commodity prices. However, in 2023, exports will decline to USD 275.1 billion due to falling commodity prices and uncertainty in the global economy. The main problem facing Indonesia is its dependence on certain commodities, which makes it vulnerable to price fluctuations and market changes. The aim of this research is to explore Indonesia's potential to increase exports through the application of the theory of comparative advantage, Heckscher-Ohlin theory, and the theory of Economic Scale and Diversification to identify factors that influence export performance, including trade policy, infrastructure and technology. The method used in this research is qualitative with a literature study approach, which allows in-depth analysis of data and information from various sources. The research results show that although Indonesia has a comparative advantage in natural resources, challenges such as dependence on certain commodities, global price fluctuations, and inadequate infrastructure hamper export performance